Video-assisted thoracoscopic cardiac denervation of refractory ventricular arrhythmias and electrical storms: a single-center series (2019)
The combined treatment of beta-blockers with ablation and Implanted cardioverter defibrillation therapy, continues to be the mainstay treatment for ventricular arrhythmias (VAs). Despite treatment, some patients remain refractory. Recent studies have shown success rates using video-assisted thoracoscopic (VATS) cardiac denervation as an effective therapeutic option for these patients.